IELTS preparation and practice : reading and writing : academic module - Sahanaya, Wendy, 1940-; Lindeck, Jeremy; Stewart, Richard (Melbourne : Oxford University Press, 1998)
The reading test. The writing test. Test tips.
Keywords: English language; International English Language Testing Systems; English language -- Examinations; International English Language Testing System; English language -- Examinations, questions, etc